Efeitos da exposição materna ou paterna ao disselento de difenila sobre o desenvolvimento intra-uterino da prole de ratas wistar - Favero, Alexandre Marafon (2006)
Selenium (Se) is an essential trace element for man and is known for its role in regulating growth and development of the fetus and newborn. Furthermore, Se is a micronutrient required for normal spermatogenesis and, therefore, essential for normal male reproductive function. However, it is well known that this element, depending of dose, can be highly toxic to several species of animals. Diphenyl diselenide [(PhSe)2] is a Se-compound widely used as intermediate in organic synthesis, as a consequence, the risk of human exposure to this chemical at the workplace may increase. Several studies demonstrated that (PhSe)2 is an organoselenium compound with potential therapeutic use. The present study evaluates the effects of single maternal subcutaneous injection of 50 and 100 mg/kg (PhSe)2 at gestational days (GD) 6, 10 or 17 in Wistar rats (article 1). The highest dose of (PhSe)2 was also administered at GD7-12. External and internal fetal soft-tissue examination was performed at GD20. No mortality was observed in fetuses or dams at any (PhSe)2 treatment. Neither did exposure to (PhSe)2 cause significant changes to fetal body weight, organ weight, or fetal size when dministered at GD6-8, 10-12 or 17. Exposure to 100 mg/kg (PhSe)2 at GD 9 produced significant changes in fetal biometry (crown-rump (CR) length) and body weight. No increase in the proportion of fetuses with external visible abnormalities was observed in groups exposed to (PhSe)2. Skeletal anomalies were observed in fetuses in the GD 9-11 treatment groups and included incomplete ossification of cranial bones, misshapen and incomplete ossification of sternebrae, reduced sternebrae number, wavy and extra ribs, incomplete ossification of fore and hindpaw bones and incomplete ossification of sacral and caudal bones. We conclude that maternal administration of (PhSe)2 during GD 7-12 led to increased incidences of these skeletal variations or anomalies, but did not cause externally visible malformations in rat fetuses. Another focus of this study was the evaluation of the effect of paternal exposure to (PhSe)2 on the development of progeny of Wistar male rats (article 2). Male rats were exposed to (PhSe)2 subcutaneously for 4 weeks (wk) at the dose of 5.0 mg/kg and 8 weeks at the dose of 2.5 mg/kg, prior to mating with unexposed females. No lethality was noted in any group. At term of exposure period, 4-wk-exposed male rats presented significant decrease in the body weight. Sex organ weights were similar in (PhSe)2-exposed and control male groups. The number of implantation sites in females mated with males exposed to (PhSe)2 for 8-wk was significantly higher than those of the respective control group. Male exposure to (PhSe)2, administered for 4- and 8-wk, did not change fetal body weight. Gross examination of fetuses from 4- and 8-wk-exposed groups did not reveal the appearance of external anomalies. Examination of live fetuses for ossification centers did not show any significant difference between groups. No increase in the incidence of skeletal anomalies was observed in fetuses obtained from females impregnated with (PhSe)2-exposed males. The current study indicated that (PhSe)2 given sub-chronically (4 or 8 weeks) to male rats had no adverse effects on their progeny. On the basis of results mentioned above, it is possible conclude that (PhSe)2 is a compound with low developmental toxicity, since adverse effects observed were only manifested at a high level dose. Of particular importance, (PhSe)2 possess its pharmacological properties at doses lower than these tested here.